An Evaluation of Habitat Uses and Their Implications for the Conservation of the Chinese Bumblebee Bombus pyrosoma (Hymenoptera: Apidae) - Hu, Xiao; Liu, Jiyao; Ding, Guiling; Naeem, Muhammad; Li, Jilian; Ma, Fangzhou; Huang, Jiaxing; An, Jiandong (Frontiers in Ecology and Evolution, 2021)
Bumblebees are important pollinators for many wild plants and crops. However, the bumblebee populations are seriously declining in many parts of the world. Hence, the bumblebee conservation strategy should be urgently addressed, and the species distribution modeling approach can effectively evaluate the potentially suitable areas for their conservation. Here, one of the most abundant and endemic species of bumblebee in China, Bombus pyrosoma, was selected to assess the influence of current and future climates on its distribution with MaxEnt. Nine high-resolution bioclimatic/environmental variables with high contribution rates and low correlations were used. Four of the nine bioclimatic/environmental variables, min temperature of the coldest month (bio_06), annual mean temperature (bio_01), precipitation of wettest month (bio_13) and radiation of warmest quarter (bio_26), were found to be the most critical factors influencing the distribution of B. pyrosoma. The modeling results showed that the areas with high and moderate suitability for B. pyrosoma covered 141,858 km2 and 186,198 km2 under the current climate conditions. More than 85% of the sampling sites in 2019 were found to be suitable under the current scenario. Under the future A1B and A2 scenarios in 2050 and 2100, the areas with low and moderate suitability for B. pyrosoma increased. However, alarmingly, the high suitability areas decreased under the future A1B and A2 scenarios in 2050 and 2100. Furthermore, regions covering seven provinces of northern China were found to be the most crucial for developing nature reserves for B. pyrosoma, with the following order of suitable areas: Gansu, Shanxi, Ningxia, Qinghai, Shaanxi, Hebei and Beijing. Our study highlights the impact of future climate changes on the distribution of B. pyrosoma, and conservation strategies should mitigate the threats posed by environmental changes, particularly in the current high suitability areas.